Research Methodology - Mohd Nazri, Anis Husna; Suhaimi, Hanis Najeha; Nik Mohd Shaharil, Nik Anis Sabrina; Nik Zulkipli, Nik Muhammad Ifwat; Zainal Fitri, Nurain Nafisa; Azmin, Aida Kesuma; Musra, Nur Arifah (KAED Universal Design Unit (KUDU), 2022)
Chapter two will focus on the methodology in documenting the findings on Masjid Jamek Sultan Abdul Samad. This chapter would discuss the distribution of work among the members of the Sutera heritage group and the methods in collecting data in depth. The works were done during the fieldwork and in the architecture studio in the span time of seven weeks.